(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This research paper examines the historical origins and development of the Jangi dance genre. This dance plays a significant role in reflecting the heroic spirit of Turkic peoples, having traditionally been performed during various competitions and ceremonial festivities. The study offers a detailed classification of two primary forms of the Jangi dance: the ashugh-type and the choreographic (dance) Jangi. The article highlights the deep-rooted traditions of public celebrations and festivals among Turkic communities, emphasizing their cultural continuity.Jangi melodies continue to be performed in everyday life during street performances (such as zorkhana shows), competitive events (including horse racing), and similar gatherings. The musical accompaniment—typically performed on the zurna—amplifies the heroic and combative character of these events. The study also notes the existence of analogous collective dances within the folk music traditions of several Turkic peoples. Although these dances may differ in name, they are similar in nature and spirit due to their heroic themes. In Azerbaijan, variations of the Jangi dance also exist that are associated with specific khanates, tribes, and folk heroes. While many of these forms have been forgotten or lost over time, a few examples have survived in popular memory and practice. Prominent Azerbaijani composers such as Uzeyir Hajibeyli, Suleyman Alasgarov, Agshin Alizadeh, Vasif Adigozalov, among others, have shown great interest in the Jangi genre. They not only integrated traditional Jangi melodies into their works but also composed original pieces in this style, encompassing both large-scale and smaller musical forms.